2022
DOI: 10.1002/pssb.202200079
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity and Piezoelectric Response of (Sc,Y)N/(Al,Ga,In)N Monolayer Alternating Stacked Structures by First‐Principles Calculations

Abstract: Group III‐nitrides with doping recently attract great interest because of their outstanding ferroelectric and piezoelectric properties. Herein, the spontaneous polarization and piezoelectricity of the wurtzite III‐nitrides (AN, A = Al, Ga, In) with the rare earth element (R = Sc, Y) doping (w‐R0.5A0.5N) are investigated by first‐principles calculations. The polar w‐R0.5A0.5N and nonpolar h‐R0.5A0.5N are stable, which is proved by the elastic constants and phonon band structures. The w‐Sc0.5In0.5N and w‐Y0.5In0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In 2022, Yazawa et al suggested that the strain sensitivity of switching barrier is one order of magnitude larger than that of the spontaneous polarization in wurtzite nitride ferroelectrics (figures 11(d) and (e)) [141]. Except for random Sc-III-N alloys, ferroelectric polarization switching properties in ScN/III-N superlattice has been also predicted by Noor-A-Alam et al [142], Sun et al [128], and Jiang et al [143] recently.…”
Section: Theoretical Prediction Of Ferroelectricity In Nitridesmentioning
confidence: 81%
See 2 more Smart Citations
“…In 2022, Yazawa et al suggested that the strain sensitivity of switching barrier is one order of magnitude larger than that of the spontaneous polarization in wurtzite nitride ferroelectrics (figures 11(d) and (e)) [141]. Except for random Sc-III-N alloys, ferroelectric polarization switching properties in ScN/III-N superlattice has been also predicted by Noor-A-Alam et al [142], Sun et al [128], and Jiang et al [143] recently.…”
Section: Theoretical Prediction Of Ferroelectricity In Nitridesmentioning
confidence: 81%
“…Such an enhancement in ScInN, however, has not been reported yet. Recent experiments and calculations also showed that BAlN and yttrium (Y) alloyed III-nitrides could be ferroelectric [114,128]. Since all ferroelectrics are piezoelectric, it would be advantageous to explore the piezoelectric response limit in those emerging materials [129][130][131].…”
Section: Piezoelectricitymentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 It should be pointed out that ScAlN is compatible with CMOS technology even in harsh environments. [18][19][20]…”
Section: Overview Of Scaln As An Emerging Ferroelectric Materialsmentioning
confidence: 99%